ANALYSIS OF THE IMPLEMENTATION OF ACCOUNTING AND THE USE OF ACCOUNTING INFORMATION IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) - Arani Tri Kinasih; Maulida Karimah; Nur Hikmah; Dessy Ferditha; Zara Tania Rahmadi; Indra Setiawan (Bridging Journal of Islamic Digital Economics and Management, 2024)
This research aims to analyze how accounting is implemented and the use of accounting information in MSMEs that take part in the APINDO DKI Jakarta program. This research method uses a descriptive qualitative method with a case study approach. The objects of this research were collected from 11 MSMEs from various types of businesses that participated in the APINDO DKI Jakarta program. Questionnaires were used to collect data used in this research. The results of this research reveal that although accounting is an important decision-making tool in companies, many MSMEs do not utilize the full potential of accounting practices. APINDO DKI Jakarta MSME accounting records have been implemented, although they are still simple. This is caused by several factors, including limited knowledge, resources and access to accounting technology. The financial reports prepared are in the form of profit/loss reports, balance sheets and cash flow reports. MSMEs in the APINDO DKI Jakarta program already use accounting information in the form of operations information, management information and financial information which play an important role in supporting the success and growth of MSMEs.